2020
DOI: 10.4081/or.2020.8457
|View full text |Cite
|
Sign up to set email alerts
|

Critical shoulder angle is intrinsically associated with the development of degenerative shoulder diseases: A systematic review

Abstract: Aim of this study was to investigate the potential influence of Critical Shoulder Angle (CSA) as a predisposing factor for the development of degenerative full-thickness rotator cuff tears (DRCT) or primary glenohumeral osteoarthritis (PGOA). A systematic review of the Pubmed, Scopus, Mendeley, ScienceDirect and the Cochrane Central Register of Controlled Trials online databases was performed for literature regarding CSA and its association with DRCT and PGOA. In order to evaluate solely the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
0
9
0
2
Order By: Relevance
“…While MR-derived CT-like images provided additional information on the osseous structures of the glenohumeral joint in our study, the creation of simulated radiographs may be an important technique in order to acquire radiation-free radiograph-like images of the glenohumeral joint, especially in young patients if no radiograph or CT has been performed previously. Semi-quantitative shoulder joint assessment scores and angle measurements performed using simulated radiograph-like images may be useful for the evaluation of the osseous structures of the shoulder for therapy planning and monitoring [ 20 ]. This MR-based technique may lead to less use of conventional radiographs and CT scans in the future, since the diagnostic information could be acquired in one examination using MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…While MR-derived CT-like images provided additional information on the osseous structures of the glenohumeral joint in our study, the creation of simulated radiographs may be an important technique in order to acquire radiation-free radiograph-like images of the glenohumeral joint, especially in young patients if no radiograph or CT has been performed previously. Semi-quantitative shoulder joint assessment scores and angle measurements performed using simulated radiograph-like images may be useful for the evaluation of the osseous structures of the shoulder for therapy planning and monitoring [ 20 ]. This MR-based technique may lead to less use of conventional radiographs and CT scans in the future, since the diagnostic information could be acquired in one examination using MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has indicated that underlying coronal plane variation is implicated in the progression of shoulder degeneration to either OA or RCTs, with previous findings with respect to the CSA replicated in this study. 8 , 10 , 18 , 19 , 33 , 34 , 39 , 47 , 53 , 57 This article sought to further understanding of axial plane scapular morphology and association with posterior wear patterns of OA. Glenoid RV has been suggested to be associated with posterior subluxation of the humeral head and type-B glenoid pattern of degenerative wear.…”
Section: Discussionmentioning
confidence: 99%
“…This sample size was reached based on similar studies conducted. 34 , 43 , 47 , 49 Group characteristics were defined by the scans displaying type-B2 OA, rarest of the studied pathologies. Twenty B2 glenoids were added to 20 B1 glenoids chosen by order of the scan date, to create a group of 40 type-B glenoids.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations